2020
DOI: 10.1093/ehjci/ehaa946.3815
|View full text |Cite
|
Sign up to set email alerts
|

Lower plasma melatonin levels predict worse long-term survival in pulmonary arterial hypertension

Abstract: Background Exogenous melatonin has been reported to be beneficial in the treatment of pulmonary hypertension (PH) in animal models. Multiple mechanisms may be involved, with melatonin exerting anti-oxidant and anti-inflammatory effects, as well as inducing vasodilation and cardio-protection. However, endogenous levels of melatonin in treatment-naïve pulmonary arterial hypertension (PAH) patients and their clinical significance are still unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“… 11 It has been reported that abnormal circulating melatonin concentration could be used as a biomarker of different disorders, including long-term survival in pulmonary arterial hypertension and hip fracture patients with and without delirium. 12 , 13 Considering the diagnostic and prognostic effects of plasma melatonin in IDD, it could be used as an indicator for IDD development and progression. In this study, we conducted a case–control study to detect the diagnostic effects for IDD.…”
Section: Introductionmentioning
confidence: 99%
“… 11 It has been reported that abnormal circulating melatonin concentration could be used as a biomarker of different disorders, including long-term survival in pulmonary arterial hypertension and hip fracture patients with and without delirium. 12 , 13 Considering the diagnostic and prognostic effects of plasma melatonin in IDD, it could be used as an indicator for IDD development and progression. In this study, we conducted a case–control study to detect the diagnostic effects for IDD.…”
Section: Introductionmentioning
confidence: 99%